Republic of Mozambique Agrarian Sector Transformation : A Strategy for Expanding the Role of the Private Sector - World Bank Group (World Bank, Washington, DC, 2019)
The Government of Mozambique is seeking to achieve its strategic objectives and targets for socio-economic and political development by intensifying the implementation of its five-year government plan (PQG). It is also taking preparatory steps for the next phase of its PQG, which coincide with the new government period following the national elections taking place in 2019. While the Government has a stated policy of promoting an expanded role for the private sector in all sectors of the economy, it has not yet articulated a comprehensive and integrated private sector strategy for the country overall, nor for any of the major sectors/subsectors. The Government therefore has been looking to bring in international experience and expertise to help formulate, implement and track a coherent private sector strategy that is attuned to the evolving institutional roles and arrangements that are influencing the direction and pace of private sector development, both domestically and abroad. Given the dominant role of the agrarian sector in Mozambique’s economy, and in providing work for the majority of its labor force (about 80 percent), any efforts to expand the role of the private sector are likely to have their greatest impact when applied to Mozambique’s agrarian sector, which is the focus of this report. It also addresses the challenge of encouraging the private sector to expand its role in transforming Mozambique’s agrarian sector into a more productive and competitive sector.